Liver-inherent immune system: its role in blood-stage malaria - Wunderlich, Frank; Al-Quraishy, Saleh; Dkhil, Mohamed A. (Frontiers in Microbiology, 2014)
The liver is well known as that organ which is obligately required for the intra-hepatocyte development of the pre-erythrocytic stages of the malaria-causative agent Plasmodium. However, largely neglected is the fact that the liver is also a central player of the host defense against the morbidity- and mortality-causing blood stages of the malaria parasites. Indeed, the liver is equipped with an unique immune system that acts locally, however with systemic impact. Its main ‚antipodal’ functions are to recognize and to generate effective immunoreactivity against pathogens on the one hand, and to generate tolerance to avoid immunoreactivity with ‚self’ and harmless substances as dietary compounds on the other hand. This review provides an introductory survey of the liver-inherent immune system: its pathogen recognition receptors including Toll-like receptors and its major cell constituents with their different facilities to fight and eliminate pathogens. Then, evidence is presented that the liver is also an essential organ to overcome blood-stage malaria. Finally, we discuss effector responses of the liver-inherent immune system directed against blood-stage malaria: activation of Toll-like receptors, acute phase response, phagocytic activity, cytokine-mediated pro- and anti-inflammatory responses, generation of ‚protective’ autoimmunity by extrathymic T cells and B-1 cells, and T cell-mediated repair of liver injuries mainly produced by malaria-induced overreactions of the liver-inherent immune system.